Macroeconomic Effects of Market Structure Distortions : Evidence from French Cartels - Moreau, Flavien (IMF Working Papers; Working Paper ;, 2022)
We provide systematic evidence on cartels' characteristics, using novel data on cases investigated by the French Competition Authority. These practices are widely spread across sectors and cartel members are typically among the top firms in their industries. In a model with heterogeneous firms and collusion, cartels amplify misallocation by charging supracompetitive markups. Breaking down French cartels would increase aggregate productivity by 2%, welfare by 3.5%, bringing the economy 37% closer to the efficient frontier. These numbers shed light on the aggregate importance of collusion.